ENT 300 Brick and Cement Supplier / Cassandra Ubar Felix George... [et al]. - Felix George, Cassandra Ubar; Ismail, Nurbasyirah Nabila; Sa'adi, Nurzalikha; Wan, Hamilton; Raduan, Arjuna (2010)
Nowadays, there are a lot of construction going on here in Kuching and needs plenty supply of bricks and cement. Our company is located at Kola Samarahan, Kuching. In this growing education area, there a lot of students as well as their families staying here. Some of them may need renovation in future to enlarge the existing houses. Therefore, we have decided to set up a which major supply in bricks and cement to fullfill the needs of construction and renovation works that require the use of cement and bricks, We purposely choose the name "BRICK AND CEMENT SUPPLIER” to ease the contractors to find company that supply these construction material. The form of our business is partnership.